2010
DOI: 10.1111/j.1467-2995.2010.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anaesthesia (TIVA) with propofol-fentanyl and propofol-midazolam combinations in spontaneously-breathing goats

Abstract: Objective To compare the efficacy and cardiopulmonary effects of propofol and fentanyl, with propofol and midazolam for total intravenous anaesthesia.Study Design Prospective, randomized, crossover experimental study.Animals Six healthy goats; 3 does and 3 wethers. ). MethodsCardiopulmonary function was well maintained with both treatments. Recovery times in minutes from the end of anaesthetic infusion for treatments FP and MP respectively were; to extubation 3.0 (3.0-3.0) and 4.5 (3.3-5.0); to sternal positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 9 publications
4
33
2
Order By: Relevance
“…Thus, the drug chosen was fentanyl, using an infusion rate of 0.001mg kg -1 hour -1 as indicated by TRANQUILLI et al (2007). After beginning the infusion, the HR increased significantly in both groups, remaining high throughout the infusion period, which was in contrast to the findings by DZIKITI et al (2010), who observed no increase in HR when using propofol and fentanyl or midazolam infusion in goats. A possibility accounting for such a difference might be related to the higher infusion rate (12mg kg -1 hour -1 and 0.02mg kg -1 hour -1 ) of drugs (propofol and fentanyl, respectively) used in the aforementioned study, which mediated a decrease in HR during the infusion, albeit without statistically, significant differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, the drug chosen was fentanyl, using an infusion rate of 0.001mg kg -1 hour -1 as indicated by TRANQUILLI et al (2007). After beginning the infusion, the HR increased significantly in both groups, remaining high throughout the infusion period, which was in contrast to the findings by DZIKITI et al (2010), who observed no increase in HR when using propofol and fentanyl or midazolam infusion in goats. A possibility accounting for such a difference might be related to the higher infusion rate (12mg kg -1 hour -1 and 0.02mg kg -1 hour -1 ) of drugs (propofol and fentanyl, respectively) used in the aforementioned study, which mediated a decrease in HR during the infusion, albeit without statistically, significant differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, the values reported during the infusion period corroborated with those of: GUERRERO & NUNES, (2003) The G F prolonged recovery times when the animal was positioned in both sternal recumbency and in a standing position, revealing significant differences between the groups only during the SP time. These results go against the findings reported by DZIKITI et al (2010), who observed no significant differences in the recovery time when combining propofol infusion with the adjunctive administration of midazolam or fentanyl in goats. Those authors also reported that goats from the fentanyl group showed signs of disparate behavior at the time of recovery, displaying unrest, which was also observed in the present study in the animals in group G F .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…of anesthesia but their dogs were premedicated with intramuscular acepromazine (up to 0.5 mg/kg) and subcutaneous carprofene (4 mg/kg) administration. Dzikiti et al [20] found that a propofol/fentanyl infusion for 90 min. did not require assisted respiration, but recovery was not always smooth in goats.…”
Section: Discussionmentioning
confidence: 99%